How to Probe Sensory Substitution Experience? The Enactive Torch Studies - Magdalena Reuter; Weronika Kałwak; Michał Sznajder; Michał Wierzchoń (Analiza i Egzystencja)
Sensory Substitution (SS) is a situation when information from one sensory modality is translated into another, such as, e.g., from vision to touch or hearing. This is possible thanks to sensory substitution devices, which include Colorophone, EyeMusic or Enactive Torch. Sensory Substitution Experience (SSE) has not yet been described successfully. There is an ongoing debate about what kind of expe- rience is associated with SS—is it similar to a substituted sense such as vision, or a substituting sense such as hearing or touch, or perhaps different senses or a completely new sense? Here we present three studies using visual-to-tactile Sen- sory Substitution Devices (SSDs) that aim to answer these questions. In the studies, we used the Enactive Torch device, which translates information about the dis- tance from the object into vibrations. The results from qualitative and quantitative methods show that SSE is based on, but not reduced to, visual and tactile qualities. Our participants reported experiences not only related to the substituting and substituted modalities, but also to other modalities such as echolocation, hearing, sense of space, sense of orientation or cross-modal experiences. The task required a method that was standardized enough to allow data generalization but also open- ended to capture the variability of SSE qualities and their dynamics. The studies allowed us to construct a standardized method combining a standardized environ- ment and qualitative and quantitative methods to study the SSE. We also provided guidelines for SSE interviews.